2018
DOI: 10.7567/jjap.57.04fe03
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of three-dimensional-triple-level cell and two-dimensional-multi-level cell NAND flash hybrid solid-state drives

Abstract: In order to improve performance of solid-state drives (SSDs), hybrid SSDs have been proposed. Hybrid SSDs consist of more than two types of NAND flash memories or NAND flash memories and storage-class memories (SCMs). However, the cost of hybrid SSDs adopting SCMs is more expensive than that of NAND flash only SSDs because of the high bit cost of SCMs. This paper proposes unique hybrid SSDs with twodimensional (2D) horizontal multi-level cell (MLC)/three-dimensional (3D) vertical triple-level cell (TLC) NAND f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…45 Hybrid SSDs that consist of single bit cells and multistates cells have been proposed to provide a trade-off between density and reliability. 46,47 Furthermore, some efforts have demonstrated that NMSM based on the charge effect can be extended to a carbon nanotube, 48 nanocrystals, 49,50 nanowires, 51 two-dimensional materials, 52−55 and organic materials. 56−59 3.…”
Section: Flash Nmsmmentioning
confidence: 99%
See 1 more Smart Citation
“…45 Hybrid SSDs that consist of single bit cells and multistates cells have been proposed to provide a trade-off between density and reliability. 46,47 Furthermore, some efforts have demonstrated that NMSM based on the charge effect can be extended to a carbon nanotube, 48 nanocrystals, 49,50 nanowires, 51 two-dimensional materials, 52−55 and organic materials. 56−59 3.…”
Section: Flash Nmsmmentioning
confidence: 99%
“…Besides, data stored in discrete charge trapping sites were reported in silicon nitride or metal nanoparticles. Another effort is to extend memory window based on amorphous In–Ga–Zn–O thin-film transistors , with a dual-gate cell . Hybrid SSDs that consist of single bit cells and multistates cells have been proposed to provide a trade-off between density and reliability. , Furthermore, some efforts have demonstrated that NMSM based on the charge effect can be extended to a carbon nanotube, nanocrystals, , nanowires, two-dimensional materials, and organic materials. …”
Section: Flash Nmsmmentioning
confidence: 99%